An Overview of Musculoskeletal Disorders (MSDs) Complaints Among First-Semester Students of the Biology Department FST Pattimura University, 2024 - Tarangi, Filep Marfil; Ramadhany, Muhammad Reza; Kaliky, Arief Rahman S; Embisa, Yushar A; Ukratalo, Abdul M (Futurity Medicine, 2025)
Aims: Musculoskeletal Disorders (MSDs) complaints are a common health issue experienced by many individuals, including students who are in the transition phase of higher education. The leading causes of MSD complaints among first-year students are often related to poor posture while studying, the use of non-ergonomic technology, and high academic stress. This study aims to describe the complaints of Musculoskeletal Disorders (MSDs) among first-year students Methodology: The research design used in this study is a correlational design with a cross-sectional approach. The sample consists of 76 respondents. Data was collected using a questionnaire distributed through a Google Form, which was shared online and filled out by the respondents. The data from the study were analyzed using the SPSS program Results: The results indicate that there is no relationship between gender, age, smoking habits, and exercise habits with MSD complaints. However, a relationship was found between Body Mass Index (BMI) and MSD complaints Conclusion: The most common MSD complaints among students are pain in the upper neck, left shoulder, waist, buttocks, left and right ankle, and wrists